Determination of the antibiotic minocycline by integrated optofluidic microstructured polymer optical fiber chemiluminescence. Issue 6 (2nd November 2021) - Li, Zhanao; Yang, Xinghua; Teng, Pingping; Kong, Depeng; Gao, Shuai; Liu, Zhihai; Yang, Jun; Gao, Danheng; Luo, Meng; Wen, Xingyue; Yuan, Libo; Li, Kang; et al.
Abstract: An in-fiber optofluidic chemiluminescence (CL) device is reported based on a low-cost microstructured polymer optical fiber (mPOF). The mPOF is composed of a central hole for liquid delivery and a suspended core for optical coupling. Due to the lower processing temperature of mPOF, the difficulty of constructing microfluidic channels is greatly reduced. In addition, the large core diameter of mPOF is more conducive to optical coupling. The microholes are opened on the surface of the mPOF by partial melting to complete the construction of the microfluidic channel. Simultaneously, the response of the CL reaction is detected on-line by the optoelectronic device. Minocycline (MC) was employed as the analyte for on-line optofluidic CL detection. The results show that the device detects aqueous minocycline from 0.0001 to 0.1 g/L with a linear response between 0.001 and 0.01 g/L. The limit of detection is 0.0001 g/L. Moreover, the ability of the device to detect minocycline in blood serum is investigated. The relative deviation from the linear calibration value is within 3.2%. Furthermore, the low-cost in-fiber optofluidic CL device may be integrated with other devices and offers potential in drug safety and medical detection.